2013
DOI: 10.1038/aps.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits AP-2γ-induced apoptosis in the human malignant testicular germ cells in vitro

Abstract: Aim: To investigate the effects of curcumin on proliferation and apoptosis in testicular cancer cells in vitro and to investigate its molecular mechanisms of action. Methods: NTera-2 human malignant testicular germ cell line and F9 mouse teratocarcinoma stem cell line were used. The anti-proliferative effect was examined using MTT and colony formation assays. Hoechst 33258 staining, TUNEL and Annexin V-FITC/PI staining assays were used to analyze cell apoptosis. Protein expression was examined with Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Studies have demonstrated that Akt pathway is a pro‐survival pathway by activating pro‐survival signal cascades and inhibiting apoptotic signal cascades . To examine the underlying mechanisms of cordycepin resistance, the PI3KAkt/mTOR and related pathways for surviving in attached and suspended MA‐10 cells were carried out after 24‐hour cordycepin treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that Akt pathway is a pro‐survival pathway by activating pro‐survival signal cascades and inhibiting apoptotic signal cascades . To examine the underlying mechanisms of cordycepin resistance, the PI3KAkt/mTOR and related pathways for surviving in attached and suspended MA‐10 cells were carried out after 24‐hour cordycepin treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that Akt pathway is a pro-survival pathway by activating pro-survival signal cascades and inhibiting apoptotic signal cascades. [30][31][32] To examine the underlying mechanisms of cordycepin resistance, the PI3KAkt/ mTOR and related pathways for surviving in attached and suspended MA-10 cells were carried out after 24-hour cordycepin treatments. Results showed that the phosphorylation of Akt and mTOR in attached MA-10 cells were induced more by cordycepin as compared to the suspended MA-10 cells (Figure 7A,B).…”
Section: Cordycepin Resistance In Ma-10 Cells Is Mediated By Activamentioning
confidence: 99%
“…It has been reported that curcumin (5, 10 and 15 μM) inhibited the viability of NTera-2 human malignant testicular germ cells (Zhou et al 2013). Curcumin has been revealed to inhibit the colony formation in both NTera-2 and F9 mouse teratocarcinoma stem cells.…”
Section: Th E Eff Ect Of C Longa and Curcumin On Male Reproductive Smentioning
confidence: 96%
“…Curcumin has been revealed to inhibit the colony formation in both NTera-2 and F9 mouse teratocarcinoma stem cells. It has been proposed that curcumin (15 μM) can suppress AP-2γ, a marker of testicular germ cell tumors, and inhibit amplifi cation and expression of NTera-2 cells (Zhou et al 2013). …”
Section: Th E Eff Ect Of C Longa and Curcumin On Male Reproductive Smentioning
confidence: 99%
“…The cells were stained with (1) PI, a vital dye that incorporates preferentially in dead cells, (2) annexin V, a protein binding to membrane PS residues, externalized during apoptosis. The total apoptosis ratio was the sum of the early apoptotic and late apoptotic ratios (Zhou et al 2013). As shown in Fig.…”
Section: Effect Of Tmp On Ogd-induced Apoptosis In Bmecsmentioning
confidence: 99%